(1) Pf.
\[
C_n^k=\frac{n(n-1)\cdots(n-k+1)}{k(k-1)\cdots 2\cdot 1}=\frac{n}{k}C_{n-1}^{k-1}.
\]
于是
\[
\sum_{k=1}^{n}kC_n^k=\sum_{k=1}^{n}k\cdot\frac{n}{k}C_{n-1}^{k-1}=\sum_{k=1}^{n}nC_{n-1}^{k-1}\stackrel{i=k-1}{=}n\sum_{i=0}^{n-1}C_{n-1}^{i}=n 2^{n-1}.
\]
(2)
\[
C_n^k=\frac{n(n-1)(n-2)\cdots(n-k+1)}{k(k-1)(k-2)\cdots 2\cdot 1}=\frac{n(n-1)}{k(k-1)}C_{n-2}^{k-2}.
\]
于是
\[
\sum_{k=2}^{n}C_n^k C_k^2=\sum_{k=2}^{n}\frac{k(k-1)}{2}\cdot\frac{n(n-1)}{k(k-1)}C_{n-2}^{k-2}=\frac{n(n-1)}{2}\sum_{k=2}^{n}C_{n-2}^{k-2}\stackrel{i=k-2}{=}C_n^2 \sum_{i=0}^{n-2}C_{n-2}^{i}=C_n^2 2^{n-2}.
\]